Photography Training and Writing Skills for Meaning/Photo Messages with Communicative Language fo Excellent Nurul Ikhlas High School Students - Cindi Adelia Putri Emas; Ermi Rosmita (Outline Publisher, 2024)
Community service activities with the theme